CREDIT CARDS’ CONTROL IN COSTA RICA - Chaves González, Luis Alberto (2013)
This paper aims to address the issue of credit cards and the deficiencies of public policy related to that subject in Costa Rica. For that purpose, we taking into consideration the perspective of Regulations of Credit and Debit Cards, that protect rights such as confidentiality, discretion in handling data and the information right; however, it is limited in terms of regulating and promoting the financial system balance which allows cardholders protection from excessive interest rates.